Theoretical evaluation of the light distribution and PDT dose for a multi-wavelength light source - Guachamin, Victor Jesus Sanchez (2019)
The broad absorption spectrum of Protoporphyrin IX (PpIX) allows being activated by a source with an emission spectrum in the visible region. Also, PpIX can be activated simultaneously by two or more sources whose emission spectrum overlaps with its absorption spectrum. Sources with a wide spectrum of illumination, such as lamps and Sun, have a different light-tissue interaction, and the constant monitoring of the dose of light and the total damage caused by photodynamic therapy (PDT) becomes difficult. The main objectives of this study were to simulate the distribution of light in the tissue for a multi-wavelength source and determine the total theoretical photodynamic dose. This study is composed of three parts. First, photobleaching experiments of PpIX using different light sources and the development of a mathematical model was used to explain the change in PpIX concentration. Second, Monte Carlo simulation using MCX (Monte Carlo eXtreme) was performed to know the light distribution through in a human skin model. Finally, the theoretical photodynamic dose was determined using the two steps mentioned previously. The experimental results show that the decrease in the concentration of PpIX is mainly dependent on the dose of photons absorbed. Therefore, for a multi-wavelength source, the total damage is calculated by partial damages caused by each wavelength that active the PpIX. The simulation of the light distribution in the human skin phantom demonstrated that the energy fluence rate decrease as a function of the depth. The mathematical model estimates that the efficacy of PDT, where it is guaranteed there is necrosis, has a diameter and depth of about 0.3 and 0.2 mm respectively. This model can be expanded to other biological media, other photosensitizers and even to any source of illumination.